Arrow. The complete fifth season [videorecording (DVD)] - Amell, Stephen, 1981-; Cassidy, Katie, 1986-; Ramsey, David (Warner Home Video, 2017)
In Season Five, newly appointed mayor Oliver Queen finds himself challenged as he fights on two fronts for the future of Star City. With his right hand, John Diggle, back in the military and his sister Thea adamant about hanging up her vigilante hood as Speedy, Team Green Arrow is down to just Oliver and Felicity, but they are no longer the only vigilantes in town.